Nature as Text: A Systematic Review of Ecologically Themed Writing Pedagogy and Its Influence on Metacognition and Student Engagement - Lyesmaya, Dyah; Syarip Hidayat, Ujang; Abdullah Almukarom, Encep; O. Malayao Jr., Sotero (IJORER : International Journal of Recent Educational Research, 2025)
This systematic literature review (SLR) investigates how integrating ecological literacy themes into writing pedagogy influences elementary students’ metacognitive writing strategies and engagement in deep learning-oriented classrooms. The primary objective is to synthesize existing research from 2015-2025 to identify key trends, impacts, and knowledge gaps in this interdisciplinary field. Method: Adhering to PRISMA guidelines, a comprehensive search was conducted across academic databases using the PICO-S framework. Keywords included "ecological literacy," "writing pedagogy," "elementary students," "metacognition," and "engagement." Inclusion criteria focused on peer-reviewed empirical studies published between 2015 and 2025. Data extraction covered study design, population, intervention details, and key findings. A narrative synthesis approach was employed due to study heterogeneity. Results: Findings indicate a positive correlation between ecological literacy integration and enhanced metacognitive awareness in writing, alongside increased student engagement in deep learning. Contextualized writing tasks on environmental themes foster critical thinking, problem-solving, and self-regulation. Engagement is heightened by the real-world relevance of ecological topics, promoting deeper understanding and application of knowledge. Novelty: This review addresses a critical gap by specifically examining the intersection of writing pedagogy and ecological literacy, offering a unique perspective beyond traditional writing instruction. It underscores the urgency of fostering environmental awareness through early writing education, cultivating critical consciousness in students regarding climate crises, and promoting a holistic integration of academic and life literacies. This interdisciplinary approach provides novel insights for 21st-century educational practices and curriculum development.